Transaction Cost Economics and Recource Based View: complementary aspects in the treatment of governance structures - Albuquerque Augusto, Cleiciele; de Souza, José Paulo (REBRAE, 2015)
The transaction cost economics (TCE), in the field of New Institutional Economics, have been shown as one of the most elaborate theoretical and explanatory constructs of arrangements existing in organizational reality. However, recent studies have sought on the Resource Based View (RBV) approach the theoretical foundations about setting these arrangements, in addition to highlighting a required complementarity between TCE and the RVB in understanding how they are formed. In this sense, the objective in this article was to understand how the complementarity theory TCE and RBV explain the configuration of the governance structures in the context of New Institutional Economics. The discussion presented in the form of essay, demonstrated that resources and differentiated capabilities could provide the basis for the proper choice of governance structures. These structures, in turn, are chosen in order to protect and achieve sustainable competitive advantages from these resources. Thus, that the complementary view of TCE with RBV is able to encompass more fully the aspects related to the choice of firm boundaries, minimizing the individual limitations of these approaches in terms of strategic analysis.